Библиотечная деятельность Адама Мицкевича - Фирсов, Георгий (Knygotyra, 1982)
The paper describes the little known page in the biography of the Great Polish poet A. Mickiewicz, his activities as librarian, first after his graduation from the Vilnius university in the districtal school at Kaunas, than, after his left Russia, in Paris as librarian in various local libraries: Bibliotheque Nationale, the Library of Polish historical-literary Society and at last (1853–1855) in the Library of the Arsenal.